Credit and collections guidebook - Bragg, Steven M. (Colorado : Academy of Sciences, 2014)
The "Credit & Collection Guidebook" covers all of these topics and more with dozens of examples, as well as forms, templates, and references to the author's popular Accounting Best Practices podcast.
Chapter1. Credit and collection operations -- Chapter2. Credit procedures -- Chapter3. Credit controls -- Chapter4. Collection procedures -- Chapter5. Collection controls -- Chapter6. The credit policy -- Chapter7. The credit applications -- Chapter8. Customer credit ratings -- Chapter9. Ongoing credit monitoring -- Chapter10. Interpretation of financial statements -- Chapter11. Credit risk reduction -- Chapter12. Customer billings -- Chapter13. Payment handling -- Chapter14. Collection tactics -- Chapter15. Payment deduction -- Chapter16. Skip tracing -- Chapter17. The collection agency -- Chapter18. Litigation and bankruptcy tactics -- Chapter19. The allowance of doubtful accounts -- Chapter20. Credit and collection technology -- Chapter21. Product and service improvements -- Chapter22. Credit and collection measurements -- Chapter23. Credit and collection Laws .
Includes index.
Keywords: COLLECTING ACCOUNTS